ANALISA DCS (DISTRIBUTED CONTROL SYSTEM) PADA PROSES POLIMERISASI - Redaksi Tim Jurnal (Sutet, 2017)
With the growing technology in industrial markets today, many factories require DCS (Distributed Control System) to control the process equipment at the plant. DCS serves to read the response quickly on factory equipment that has been installed with the sensor. This paper will analyze the use of DCS in polymerization process at PT INDORAMA SYNTHETICS factory located in Jatiluhur - Purwakarta, West Java. In PT INDORAMA SYNTHETICS polymerization process using DCS CENTUM 3000 which can control and monitor every machine connected with DCS. With the use of DCS, PT.INDORAMA SYNTHETICS can control the flow of PTA tanks and EG tanks that produce a flow output of 10423 kg / h.